Convergence of MCR-8.2 and Chromosome-Mediated Resistance to Colistin and Tigecycline in an NDM-5-Producing ST656 Klebsiella pneumoniae Isolate From a Lung Transplant Patient in China - Jiankang Zhao; Jiankang Zhao; Ziyao Li; Ziyao Li; Yulin Zhang; Yulin Zhang; Xinmeng Liu; Xinmeng Liu; Binghuai Lu; Binghuai Lu; Bin Cao; Bin Cao; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
We characterized the first NDM-5 and MCR-8.2 co-harboring ST656 Klebsiella pneumoniae clinical isolate, combining with chromosomal gene-mediated resistance to colistin and tigecycline. The K. pneumoniae KP32558 was isolated from the bronchoalveolar lavage fluid from a lung transplant patient. Complete genome sequences were obtained through Illumina HiSeq sequencing and nanopore sequencing. The acquired resistance genes and mutations in chromosome-encoded genes associated with colistin and tigecycline resistance were analyzed. Comparative genomic analysis was conducted between mcr-8.2-carrying plasmids. The K. pneumoniae KP32558 was identified as a pan-drug resistant bacteria, belonging to ST656, and harbored plasmid-encoded blaNDM-5 and mcr-8.2 genes. The blaNDM-5 gene was located on an IncX3 type plasmid. The mcr-8.2 gene was located on a conjugative plasmid pKP32558-2-mcr8, which had a common ancestor with another two mcr-8.2-carrying plasmids pMCR8_020135 and pMCR8_095845. The MIC of KP32558 for colistin was 256 mg/L. The mcr-8.2 gene and mutations in the two-component system, pmrA and crrB, and the regulator mgrB, had a synergistic effect on the high-level colistin resistance. The truncation in the acrR gene, related to tigecycline resistance, was also identified. K. pneumoniae has evolved a variety of complex resistance mechanisms to the last-resort antimicrobials, close surveillance is urgently needed to monitor the prevalence of this clone.